Rational Generation of Fe-N-x Active Sites in Fe-N-C Electrocatalysts Facilitated by Fe-N Coordinated Precursors for the Oxygen Reduction Reaction - Kim, Minhyoung; Yoo, Ji Mun; Ahn, Chi-Yeong; Jang, Jue-Hyuk; Son, Yoon Jun; Shin, Heejong; Kang, Jiho; Kang, Yun Sik; Yoo, Sung Jong; Lee, Kug-Seung; Sung, Yung-Eun (WILEY-V C H VERLAG GMBH, 2019)
Fe-N-C catalysts synthesized by pyrolysis of Fe and N precursors have been intensively studied due to their remarkable activities for the electrochemical oxygen reduction reaction (ORR). Although Fe-N-4 coordinated structures have been suggested as active sites by recent spectroscopic studies, the influence of precursor coordination on the generation of the active sites during high-temperature pyrolysis is not well understood. In this work, phenanthroline isomers were used as systematic model precursors to reveal the correlation between precursor coordination and active site formation in Fe-N-C catalysts. Coordination between Fe and each phenanthroline isomer was effectively controlled by the molecular structure: monodentate (1,7- and 4,7-phenanthroline) and bidentate coordination (1,10-phenanthroline). Through X-ray absorption spectroscopy and X-ray photoelectron spectroscopy study, large difference in atomic distribution of both Fe and N was revealed; the preferential formation of Fe-N-x active sites was featured only in Fe(1,10-phenanthroline)/KB with homogeneously distributed Fe and highly retained pyridinic N. With Fe-N-x active site moieties, Fe(1,10-phenanthroline)/KB exhibited superior ORR activity and stability in alkaline half-cell and full-cell tests. These results highlight the importance of the use of precursors with multiple coordination (i. e. bidentate) for the effective derivation of Fe-N-x active sites for highly active and stable ORR electrocatalysts.
Keywords: METAL-ORGANIC-FRAMEWORK; PEM FUEL-CELLS; CATALYTIC SITES; IRON; CARBON; POLYANILINE; PERFORMANCE; PYROLYSIS; COMPLEXES; GRAPHENE